Political Communication Errors During The Timor-Leste Parliamentary Campaign Period Are Seen From The Logical Aspect - Silvestre de Oliveira (CV. Ulil Albab Corp, 2024)
As a country that operates the democracy system, Timor-Leste's political communication dynamics are full of pro- and non-probable political decisions carried out by political actors. Democracy has led to a more rational and more iransional political communication in Timor-Leste. Rational and iransional political communication in Timor-Leste can be analyzed from political messages conveyed by political actors as well as society's political thinking. Jurgen Hubermas, a rational political communication is a good communication skill to meet the principle of mutual understanding. Rational political communication is good, non-exclusive communication, communication that has no dominancy within it, eligalyter communication, communication based on honesty, certainty and accuracy. The current political communication in Timor-Leste, especially during the campaign period, chose both the President and the political parties for the rule, is always full of irrational political communication. The factors that lead to irrational political communication in Timor-Leste are emotional. This factor makes political communication full of political messages linked to history, race,. Insult and other political messages that are not rational. The research method used in this research is related to qualitative methods. Sugiyono (2019: 18) defines that the qualitative method is a research method based on the philosophy of post positivism used to research objects with natural conditions. This research uses data collection techniques based on the observation of the situation of Timor-Leste's political communication through both television and Face book media and relevant documentation such as journal, media and books. All the data collected will be analyzed and concluded in accordance with the Milles and Huberman data analysis diagrams. Errors in political communication in the participatory campaign period in Timor-Leste are widespread when viewed from the logical aspect. These errors are caused by the consistency of political actors in conducting rational political communication based on the vision, mission and program of the party. Given the logical aspects, political communication developed by political actors to attack one another on privacy, count the reward, count the fight against one another, and do not consider one another, each other about corruption without evidence, political all of these errors are uneducative political communication and the destruction of national interests.